Netflix Preference and the Viewership of DSTV among Babcock University Undergraduates - Ajaegbu, Oguchi O.; Akoja, Mofoluke I.; Akinsanya, Olawunmi T. (NIU Journal of Social Sciences, 2022)
Since the advent of Netflix in Nigeria in 2016, there has been a decline in the viewership of DStv channels. Existing literature have investigated the impact Netflix has on DStv in other African countries, but no study has been conducted in Nigeria especially with respect to Nigerian university undergraduates. As such, this study examined the preference of Netflix and viewership of DStv channels among Babcock university undergraduates. The study adopted the uses and gratification theory, media dependency theory and technology acceptance model for the study. The study adopted the multiple sampling methods and employed the survey research design. With the aid of a well-structured questionnaire, the research gathered data from three hundred and seventy three (373) respondents across three schools in Babcock University. The collated data were analyzed, research hypotheses tested and results presented in table format. The study found that Babcock university undergraduates generally did not have a preference and viewership of DStv (â€œdisagreedâ€) but agreed with the factors that motivate a preference for Netflix. Further investigation showed a significant gender difference in the viewership of DSTV among Babcock university undergraduates. Keywords: DStv, Netflix, Preference, Viewership, Over-the-top television